2017
DOI: 10.1073/pnas.1617959114
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of the human antibody repertoire reveals quantitative signatures of immune senescence and aging

Abstract: The elderly have reduced humoral immunity, as manifested by increased susceptibility to infections and impaired vaccine responses. To investigate the effects of aging on B-cell receptor (BCR) repertoire evolution during an immunological challenge, we used a phylogenetic distance metric to analyze Ig heavy-chain transcript sequences in both young and elderly individuals before and after influenza vaccination. We determined that BCR repertoires become increasingly specialized over a span of decades, but less pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
127
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(135 citation statements)
references
References 49 publications
(53 reference statements)
7
127
1
Order By: Relevance
“…1E). To compare the initial B cell repertoire with the reconstituted repertoire after depletion, we applied the phylogenetic distance metric UniFrac (29), whose use on immune repertoire data was recently demonstrated (30). As expected, we found that group A displayed greater preinfusion-to-postinfusion distances than group B (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1E). To compare the initial B cell repertoire with the reconstituted repertoire after depletion, we applied the phylogenetic distance metric UniFrac (29), whose use on immune repertoire data was recently demonstrated (30). As expected, we found that group A displayed greater preinfusion-to-postinfusion distances than group B (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative to computational error correction of immunosequencing datasets, biologists use unique molecular barcoding (33, 34), an experimental approach that allows one to correct most amplification and sequencing errors, thus enabling analysis of low-abundance receptor sequences (46, 9, 35, 27, 36, 37, 38). This approach is based on attaching a short unique barcode (12–17 nt) to each RNA molecule, so that all amplified copies of this molecule contain the same barcode.…”
Section: Methodsmentioning
confidence: 99%
“…The Unique Molecular Identifiers (UMIs) barcoding technology (33, 34) allows one to analyze low-abundant receptor sequences and to error-correct amplification errors (35, 27, 36, 37, 38). Barcoding and non-barcoding protocols have different requirements with respect to repertoire construction algorithms; e.g., while aggressive error-correction works well for barcoded Rep-seq datasets, it results in overcorrection and loss of natural diversity for non-barcoded datasets.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, next-generation sequencing (NGS)-based antibody repertoire analysis has been used to provide a systemic view of humoral responses to antigen stimuli [13] such as viral infections [19] and vaccination [17,20,21]. Understanding the mechanism and dynamics underlying antibody generation can facilitate vaccine design and improve the prognosis of infectious diseases [13,22].…”
Section: Introductionmentioning
confidence: 99%